The Factors Affecting Intention to Subscribe to Netflix Video on Demand Services - Resinta Evaratis; Fajar Sidiq Adi Prabowo; Muhammad Azhari (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2023)
Interest in subscribing to Netflix's video on demand service is influenced by several factors, namely service quality, price perception, promotion, customer service, subscription interest, as well as the influence of service quality, price perception, promotion, and customer care/service on interest in subscribing to video on demand services. The method used is a quantitative method. Based on conclusive objectives, survey research strategy, type of causal investigation, based on individual analysis units, researcher involvement does not interfere with the data, non-conflict background and cross-sectional research implementation time In this research, the results showed that the t-count of service quality on subscription interest was 9.992, the t-count of price perception on subscription interest was 1.999, the t-count of promotion on subscription interest was 10.889, and the t-count of customer care/service was 4,933. Based on the results of the research, it is concluded that the variables Service Quality, Price Perception, Promotion and Customer Care/Service have a positive effect on Interest in Subscribing to Netflix Video on Demand.